Изучение ориентации рыб при хоминге - Абросимова, А.М. (Вестник зоологии, 1975)
Studies in orientation of the Kiev reservoir fresh water fishes-Rutilus rutilus, Abramis brama, A. ballerus, Blicca bjoerkna, Perca fluviatilis, Esox lucius showed that season of the year, weather and distance of delivery have an influence on the fish ability to orientation. The carried out experiments permit supposing that under conditions of reservoirs vision and lateral line are the leading receptors in orientation.